PERWUJUDAN CUSTOMER ORIENTATION MELALUI PERUBAHAN SISTEM AKUNTANSI MANAJEMEN DALAM INSTITUSI JASA KEUANGAN - Wirjono, Endang Raino (KINERJA, 2003)
This article describe how financial institutions are increasingly integrating management accounting system with customer-related activities. However, several barriers related to organization structure, resources and attitudes hamper further customer-oriented changes. Activity Based Costing can used by financial service institutions, but many practitioners view this system as too complicated and time consuming. Recently, its emerge activity analysis that offering an easy solution to eliminate traditional barriers in financial services.Keywords: customers, financial services, activity analysis